Socioeconomic characteristics of the parents and the risk prediction of early childhood caries - Wahyu Aji Wibowo; Retno Indrawati Roestamadji; Retno Pudji Rahayu (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: The high prevalence of early childhood caries still becomes a major health problem. It is because children prefer to consume sweet foods, which are also cariogenic. The oral mucosa is a mirror of general health or any systemic disease which usually shows visible symptoms in the oral cavity. Dental caries in children is often related to the socioeconomic characteristics of the parents. Some references suggest that there is a relationship between the socioeconomic status with the incidence of caries. Purpose: The purpose of this study was to examine the relationship of socioeconomic characteristics of the parents with the risk prediction of early childhood caries by using cariogram approach to the elementary school students in Wonosobo. Method: The research is an observational analytic study with cross-sectional approach survey method. The research sampling uses proportional random sampling with 201 respondents of fifth graders. The socioeconomic status is measured through questionnaires, while the risk prediction of early childhood caries is measured by using cariogram. The research data analysis uses Spearman rank. Result: The results of the study show that the socioeconomic characteristics of the respondents’ parents mostly belong in the middle category as many as 145 respondents (72.1%), lower category as many as 31 respondents (15.4%) and in the upper category as many as 25 respondents (12.4%). Prediction of the respondents avoiding early childhood caries is 55%, while the prediction of the respondents being risked of having early childhood caries is 45%. The results of data analysis show that the relationship between the socioeconomic characteristics of the respondents’ parents and the risk of having early childhood caries for the respondents is p<0.05. Conclusion: There is a relationship between the socioeconomic characteristics of the respondents’ parents with the early childhood caries, which shows that the higher the socioeconomic status of the parents, the lower the risk of the respondents from having early childhood caries.